Dihydrotestosterone levels at birth associate positively with higher proportions of circulating immature/naïve CD5+ B cells in boys. Issue 1 (December 2017) - Lundell, Anna-Carin; Nordström, Inger; Andersson, Kerstin; Strömbeck, Anna; Ohlsson, Claes; Tivesten, Åsa; Rudin, Anna
Abstract Boys present with higher proportions of immature/naïve CD5+ B cells than girls up to 3 years of age. Boys also have higher fractions of regulatory T cells (Tregs) in early infancy, but the mechanisms for these sex-related differences are unknown. In the prospective FARMFLORA follow-up study of 23 boys and 25 girls, we investigated if these immunological differences remained at 8 years of age. We also examined if testosterone or dihydrotestosterone (DHT) levels at birth and at 8 years of age were associated with immune maturation. Immunological variables and androgen levels were examined and measured in blood samples obtained at birth, 3–5 days and at 8 years of age. Boys had higher proportions of CD5+ and immature/transitional CD24hi CD38hi B cells, whereas girls had higher fractions of B cells with a memory phenotype at 8 years of age. School-aged boys also presented with higher frequencies of Tregs, and a greater capacity to produce T-cell-associated cytokines. Among boys, higher cord blood DHT levels were associated with higher proportions of CD5+ B cells in early infancy and at 8 years of life. These results suggest that DHT actionsin utero might be involved in the mechanism for delayed peripheral B-cell maturation in boys.